The Australian Square Kilometre Array Pathfinder: System Architecture and Specifications of the Boolardy Engineering Test Array. (13th November 2014) - Hotan, A. W.; Bunton, J. D.; Harvey-Smith, L.; Humphreys, B.; Jeffs, B. D.; Shimwell, T.; Tuthill, J.; Voronkov, M.; Allen, G.; Amy, S.; Ardern, K.; Axtens, P.; et al.
Abstract: This paper describes the system architecture of a newly constructed radio telescope – the Boolardy engineering test array, which is a prototype of the Australian square kilometre array pathfinder telescope. Phased array feed technology is used to form multiple simultaneous beams per antenna, providing astronomers with unprecedented survey speed. The test array described here is a six-antenna interferometer, fitted with prototype signal processing hardware capable of forming at least nine dual-polarisation beams simultaneously, allowing several square degrees to be imaged in a single pointed observation. The main purpose of the test array is to develop beamforming and wide-field calibration methods for use with the full telescope, but it will also be capable of limited early science demonstrations.